Chemistry Learning Innovation: Development of Guided Inquiry-Based E-LKPD for 10th Grade Students at SMAN 2 Rambatan - Muhammad Syadam Nashyra; Elvy Rahmi Mawarnis; Mohd. Yusri Abd. Rahman (Postgraduate Program, University of Mataram, 2024)
This research is based on the low learning outcomes of students. One of the factors causing low student learning outcomes is teaching materials. Learning resources at SMAN 2 Rambatan use package books, but the school's package books are lacking, besides that bulky textbooks that make students lazy to carry the book. When viewed from teaching materials, examples of sample questions and discussions are lacking. In the learning process students only depend on the teacher's discussion. The purpose of this research is to produce valid and practical Guided Inquiry Based Electronic Student Worksheet (E-LKPD). This research uses the Research and Development research method with the 4-D development model (define, design, development, and disseminate), but the stages in the 4-D model are only carried out from the first to the third stage, namely the define, design, and development stages. This study used research instruments in the form of validation sheets and practicality questionnaires. The data analysis techniques used in this research are validity analysis techniques, practicality analysis. Furthermore, the results of the initial E-LKPD designed were continued in the validity and practicality tests. Guided Inquiry Based E-LKPD has met the valid criteria with validation results obtained 88%. Guided Inquiry-Based E-LKPD has met the practical criteria with the results of the 89% learner response questionnaire.